LC-MS/MS를 이용한 농산물 중 Kasugamycin 시험법 개발 - 이한솔; 도정아; 박지수; 조성민; 신혜선; 장동은; 정용현; 이강봉; Lee, Han Sol; Do, Jung-Ah; Park, Ji-Su; Cho, Sung Min; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2019)
An analytical method was developed for the determination of an antibiotic fungicide, kasugamycin, in agricultural products (hulled rice, potato, soybean, mandarin and green pepper) using liquid chromatographytandem mass spectrometry (LC-MS/MS). Samples were extracted with methanol adjusted to pH 13 using 1 N sodium hydroxide, and purified with a HLB (hydrophilic lipophilic balance) cartridge. Linearity of a matrix-matched calibration curve using seven concentration levels, from 0.001 to 0.1 mg/kg, was excellent with a correlation coefficient ($R^2$) of more than 0.9998. The limits of detection (LOD) and quantification (LOQ) of instrument were 0.0005 and $0.001μg/mL$, respectively, and the LOQ of analytical method calculated as 0.01 mg/kg. The average recoveries at three spiking levels (LOQ, $LOQ{×}10$, $LOQ{×}50$, n=5) were in the range of 71.2~95.4% with relative standard deviation of less than 12.1%. The developed method was simple and all optimized results was satisfied with the criteria ranges requested in the Codex guidelines and Food Safety Evaluation Department guidelines. The present study could be served as a reference for the establishment of maximum residue limits (MRL) of kasugamycin and be used as basic data for safety management relative to kasugamycin residues in imported and domestic agricultural products. 본 연구는 농산물 중 잔류허용기준 신설 예정 농약인 가스가마이신의 안전 관리를 위한 공정 시험법을 개발하기 위하여 수행되었다. 가스가마이신은 단백질 합성과정 중 번역 개시 단계를 저해하여 균의 증식을 억제하는 작용기작을 가지고 있으며 특히 사상균인 Piricularia oryzae에 의해 발병하는 도열병을 예방하는 데 효과적이다. 현재 우리나라에는 농산물 중 가스가마이신의 잔류물의 정의가 설정되어 있지 않고 모화합물 만을 잔류물의 정의로 예정하고 있다. 또한 잔류허용기준이 설정된 농산물이 없기 때문에 모든 국내 재배 농산물 또는 수입 농산물 유통 시 실시하는 잔류농약 검사에서 농약 허용물질목록관리제도(Positive List System; PLS)에 의하여 잔류량이 0.01 mg/kg 이하가 되어야 한다. 이에 농산물 중 잔류농약 분석 및 검사를 위한 공정 시험법 마련이 시급하여 본 연구에서는 대표농산물 5종(현미, 감자, 대두, 감귤, 고추)을 대상으로 시험법을 개발하고자 하였다. 따라서 수용성 유기용매인 메탄올의 적용과 수산화나트륨을 이용한 pH 조절을 통한 추출법 및 HLB 카트리지를 이용한 정제법을 최적화하여 LC-MS/MS에 의한 분석법을 확립하였다. 가스가 마이신의 시험법 정량한계는 0.01 mg/kg이며 5종의 농산물에 0.01, 0.1 및 0.5 mg/kg의 처리농도로 회수율 실험을 한 결과 평균 회수율은 71.2~95.4%이었고, 상대표준 편차는 12.1% 이하로 조사되었다. 이러한 검증 결과는 국제식품규격위원회 가이드라인(CAC/GL 40-1993, 2003)의 잔류농약 분석 기준 및 식품의약품안전평가원의 '식품등 시험법 마련 표준절차에 관한 가이드라인(2016)'에 적합한 수준임을 확인하였다. 따라서 본 연구에서 개발한 시험법은 국내 및 수입 농산물 중 가스가마이신의 안전 관리를 위한 공정시험법으로 활용될 수 있으며 잔류물의 정의 및 잔류허용기준을 설정하는 데 기초자료로써 활용 가능할 것이다.